Hubungan Masa Gestasi dengan Kejadian Ikterus Neonatorum: The Relationship Between Gestational Age and the Incidence of Neonatal Jaundice - Umi Fania Julianti (Jurnal Surya Medika (JSM), 2023)
The Infant Mortality Rate (IMR) in Indonesia has decreased every year, even though it has not yet reached the MDGs target of 23 per 1000 live births. One of the causes of infant mortality in Indonesia is due to neonatal jaundice by 6%. The incidence of neonatal jaundice at Dr. Abdul Aziz Hospital is one of the cases that often occurs every year, in 2019 there were 55 cases out of 912 newborns. The purpose of this study was to determine the relationship between gestational age and the incidence of neonatal jaundice in dr. Abdul Aziz Singkawang hospital. The design of this research is observational analytic with a retrospective approach case control design. The research sample consisted of 60 infants consisting of 30 case samples and 30 control samples. The case sampling technique was consecutive sampling and the control sample was simple random sampling. Data analysis consisted of univariate analysis by calculating percentages and bivariate analysis using chi square test. The results obtained from the chi square test results with a value of ρ value 0.000 < 005, which means that there is a significant relationship between gestational age and the incidence of neonatal infertility.